(untitled) (LEARNing Landscapes, 2015)
In this interview, Ken Zeichner describes the current changes and trends in teacher education and examines the university’s role in providing teachers with the necessary skills and knowledge. He advocates a model where the university, community, and school work together as partners to give teachers a more diversified set of knowledge and skills. This type of teacher education can be situated in the university, but it may be more effective if it takes place "outside of the bureaucracy and budget of both the university and the school system." Dr. Zeichner sees teacher research as a critical part of teacher development and firmly believes that each teacher should adopt an inquiry stance, where research is part of the practice rather than a separate activity. In conclusion, he states that, "…the old traditional forms of university-based teacher education…are not going to survive."